2019
DOI: 10.1177/0300060519826830
|View full text |Cite
|
Sign up to set email alerts
|

The learning curve in blind bedside postpyloric placement of spiral tubes: data from a multicentre, prospective observational study

Abstract: Objective This study sought to quantify the learning curve for the blind bedside postpyloric placement of a spiral tube in critically ill patients. Methods We retrospectively analysed 127 consecutive experiences of three intensivists who performed comparable procedures of blind bedside postpyloric placement of a spiral tube subsequent to failed self-propelled transpyloric migration in a multicentre study. Each intensivist’s cases were divided chronologically into two groups for analysis. The assessment of the … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
9
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
5
1

Relationship

4
2

Authors

Journals

citations
Cited by 7 publications
(9 citation statements)
references
References 35 publications
(51 reference statements)
0
9
0
Order By: Relevance
“…On the other hand, prior to the implementation of this study, training program was conducted for all the operators, including a 60-min theoretical training and operational training program of intubation procedures. In addition, previous studies have found that significant improvements in the effectiveness of all trained operators and a significant reduction in adverse events among primary intensivists as increased operating experience ( 26 ). In general, operator experience played a significant role in the success and safety of post-pyloric tube placement, and a rigorous intensive training program ensured the implementation of our study.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…On the other hand, prior to the implementation of this study, training program was conducted for all the operators, including a 60-min theoretical training and operational training program of intubation procedures. In addition, previous studies have found that significant improvements in the effectiveness of all trained operators and a significant reduction in adverse events among primary intensivists as increased operating experience ( 26 ). In general, operator experience played a significant role in the success and safety of post-pyloric tube placement, and a rigorous intensive training program ensured the implementation of our study.…”
Section: Discussionmentioning
confidence: 99%
“…Then, intensive training was given to all operators (ICU physicians and bedside nurses) involved in the study. Upon completion of the theoretical training, all operators were required to watch five tube placements and perform at least 5 procedures under the supervision of the above senior intensivist ( 26 ).…”
Section: Methodsmentioning
confidence: 99%
“…Notably, it is easier to gain the necessary expertise to perform the modified operation through training, which is conducive to its promotion. 37 …”
Section: Discussionmentioning
confidence: 99%
“…Unfortunately, neither Silva's meta-analysis nor our results demonstrated the e cacy of metoclopramide, even though three RCTs were newly included in this updated meta-analysis. Several clinical heterogeneity deriving from participants (e.g., age, comorbidities, and concomitant medication) [28][29][30], operators (e.g., years of training, profession status, and educational degree of operators) [15,31], intervention (e.g., the timing of medication, the dosage of metoclopramide, and the type of feeding tube) [12][13][14][15][16][17][18], outcome assessment (e.g., the follow-up period and the assessment personnel) [12][13][14][15][16][17][18] and the like, as well as insu cient sample sizes, may be liable for failing to establish metoclopramide's bene cial effects.…”
Section: Discussionmentioning
confidence: 99%